Potential resource and cost saving analysis of subcutaneous versus intravenous administration for rituximab in non-Hodgkin’s lymphoma and for trastuzumab in breast cancer in 17 Italian hospitals based on a systematic survey [Corrigendum] - Ponzetti C; Canciani M; Farina M; Era S; Walzer S (Dove Medical Press, 2017)
Ponzetti C, Canciani M, Farina M, Era S, Walzer S. ClinicoEconomics and Outcomes Research. 2016;8:227–233.On page 230, Table 3, first column: The last time component should be: “Patient preparation time for eighteen cycles of therapy in oncology (breast cancer)”. On page 231, Table 4, first column: The second rituximab preparation item should be: “Median time to prepare rituximab (for median number of patients per day)”. On page 231, Table 4, first column: The third item should be: “Median time to prepare trastuzumab (for each patient with eighteen therapeutic administrations)”. On page 231, Table 4, first column: The last trastuzumab preparation item should be: “Median time to prepare trastuzumab (for median number of patients per day)”. On page 232, Table 5, first column: Wording of the last outcome for each therapy should be: “Annual economic impact” rather than “Annual economic impact per patient”. On page 232, Table 5, second column: “In breast cancer (trastuzumab)”, the mean annual economic impact for the intravenous administration should be: €29,872. On page 232, Table 5, second column: The public price (hospital price) for subcutaneous administration should be: €2.89/mg. Read the original article.